The Relationship between Quality of Nursing Care and Patients’ Satisfaction in DHQ Teaching Hospital Gujranwala - Kanwal, Humaira; Choudhary, Alia Islam; Abbas, Nosheen; Yaqoob, Iqra; Bashir, Fouzia (Indus Journal of Bioscience Research, 2025)
Background: Quality nursing care is a fundamental determinant of patient satisfaction, influencing healthcare outcomes and hospital reputation. This study aimed to assess patient satisfaction with nursing care at DHQ Teaching Hospital Gujranwala, Pakistan, and identify critical factors affecting it. Methodology: A cross-sectional descriptive study was conducted among 150 hospitalized patients from intensive care, gynecology, medical, and surgical wards between September 2024 and November 2024. The Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ) was used for data collection. The questionnaire, translated into Urdu, followed a 5-point Likert scale, with total scores categorized as low, moderate, or high satisfaction. Data analysis was performed using SPSS version 25, with results presented in frequencies and percentages. Results: The majority of participants were between 36-45 years old (33.3%), with more females (54.7%) than males (45.3%). Most patients (46.6%) had a hospital stay of 3-5 days. The findings revealed that 56.6% of patients reported low satisfaction with nursing care, 30.0% had moderate satisfaction, and only 13.4% expressed high satisfaction. Conclusion: The study highlights significant gaps in patient satisfaction with nursing care, emphasizing the need for improvements in nurse-patient communication, staffing levels, and patient-centered care practices. Strengthening supervision and structured patient feedback mechanisms could enhance satisfaction levels and overall healthcare quality. Recommendations: Hospitals should focus on improving nursing communication, optimizing staffing, and conducting regular training on patient-centered care. Implementing structured feedback systems and ensuring adherence to evidence-based nursing guidelines can enhance patient satisfaction and healthcare outcomes.